2022
DOI: 10.1111/ffe.13828
|View full text |Cite
|
Sign up to set email alerts
|

Computing the durability of WAAM 18Ni 250 maraging steel specimens

Abstract: MIL-STD 1530D requires that the certification of an aircraft part employ analytical tools that are capable of modeling crack growth. It is further stated that the durability and damage tolerance (DADT) analyses should be based on linear elastic fracture mechanics (LEFM) and follow a building block approach. This paper illustrates the durability analysis required to certify an additively manufactured part by using the examples of durability tests performed on two wire arc additively manufactured (WAAM) 18Ni 250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…The author's recent paper 1 illustrated how to perform a durability analysis for an Additively Manufactured (AM) built part using as examples the test results of two WAAM 18Ni 250 Maraging steel specimens with rough "as built" surfaces where failure was due to the nucleation, and subsequent growth, of small surface-breaking cracks. The specific form of the crack growth equation used in the analysis reported by Peng et al 1 was…”
Section: The Effect Of Aspect Ratio On Durability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The author's recent paper 1 illustrated how to perform a durability analysis for an Additively Manufactured (AM) built part using as examples the test results of two WAAM 18Ni 250 Maraging steel specimens with rough "as built" surfaces where failure was due to the nucleation, and subsequent growth, of small surface-breaking cracks. The specific form of the crack growth equation used in the analysis reported by Peng et al 1 was…”
Section: The Effect Of Aspect Ratio On Durability Analysismentioning
confidence: 99%
“…In contrast, the NASA Fracture Control Handbook NASA-HDBK-5010 5 suggests using an initial aspect ratio of 1.5. In this context, it should be noted that in the durability predictions performed by Peng et al, 1 the EIDS used was a surface-breaking semi-elliptical crack with a depth of 0.254 mm and an aspect ratio c/a of 1.5. As such, the aspect ratio used was consistent with that suggested in NASA-HDBK-5010.…”
Section: The Effect Of Aspect Ratio On Durability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Practitioners in the field of additively manufactured structures have long been aware [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] that the interaction of surface-roughness with surface-breaking material discontinuities and surface-breaking porosity/lack of fusion can significantly degrade the durability and damage tolerance (DADT) of an additively manufactured part. Indeed, ref.…”
Section: Introductionmentioning
confidence: 99%
“…[7] concluded that the fatigue life of AM Ti-6Al-4V parts built using either electron beam melt or direct metal laser sintering was determined by surface roughness effects (a picture illustrating how surface-breaking cracks can develop as a result of surface-breaking material discontinuities/defects is shown in Figure 1). The author's recent paper [1] on the durability of WAAM 18NI 250 Maraging steel specimens tested with their surfaces left in the "as built" condition aptly illustrated this phenomenon in that the specimens failed due to the interaction between the rough-surface and surface-breaking material discontinuities. Although not reported in [1], this test program also found that the presence of large, wholly contained, internal voids/porosity and large near-surface voids did not result in failure.…”
Section: Introductionmentioning
confidence: 99%